Front Cover: Classification of Inflammatory Bowel Disease from Formalin‐Fixed, Paraffin‐Embedded Tissue Biopsies via Imaging Mass Spectrometry. Issue 6 (16th November 2020) - Klein, Oliver; Fogt, Franz; Hollerbach, Stephan; Nebrich, Grit; Boskamp, Tobias; Wellmann, Axel
Abstract : MALDI mass spectrometry imaging of four discriminative peptides in the two main forms of chronic inflammatory bowel disease, ulcerative colitis and Crohn's disease, as compared to normal patients. In combination with multi‐variate data analysis, this method enables an automated classification of ulcerative colitis, Crohn's disease and normal conditions tissue biopsies. This is reported by Oliver Klein, Franz Fogt, Stephan Hollerbach, Grit Nebrich, Tobias Boskamp, Axel Wellmann in arctile 1900131 .